The Policy Communication Index: a theoretically-based measure of organizational policy communication practices - Canary, Heather E.; Riforgiate, Sarah E.; Montoya, Yvonne J. (My University, 2013)
Despite recent scholarly contributions regarding policy communication, much remains to be known about policy communication processes. This article reports two studies that resulted in a survey instrument that measures policy communication in organizations. Study One included 197 full-time employees across occupations and industries. Exploratory factor analysis resulted in five factors of the Policy Communication Index: Meeting Discussions, Human Resources Communication, Coworker Interactions, Supervisor/Coworker Written Instructions, and Personal Expressions. Study Two included 245 full-time employees across job functions and industries. Confirmatory factor analysis confirmed a five-factor Policy Communication Index. Results are interpreted with structurating activity theory and implications are posed for future organizational communication research and practice.
Keywords: Structurating activity theory; Policy communication; Organizations; FMLA